PARTISIPASI POLITIK SANTRI PADA PEMILIHAN BUPATI ACEH BARAT 2017 - Sudarman Sudarman; Reza Febriandi (Jurnal Public Policy, 2017)
This research concerns to existence of Santri in dayah which are had the aim purpose to learning and deepen religious, so then very far away about the political information related then active involvement. Nevertheless, the opportunity to funneling their rights as good citizens for participate in the election uncertainly blocked, especially many of santri are beginner voters. More specifically, aim of this study to know about santri political participation in Pemilukada in Aceh Barat Regency 2017. This research uses qualitative method by involving 20 informants selected by using purposive sampling technique. The results indicated that the santri political participation is passive participatory then they had have never been directly involved in the successing of the campaign, they use only their political right to vote when voting process in TPS at the day. This participation is referred as the conventional participation form and lowest level participation hierarchy above the total apathy bit. Keywords: Participation, Political, Santri, Dayah